PREVENTIF APROACH: BAHAYA BORAK DAN CARA MENGIDENTIFIKASI MAKANAN YANG MENGANDUNG BORAK - Ira Oktaviani Rz; Alexsander Yandra (Universitas Lancang Kuning, 2017)
According to regulation of Health Minister No.033 th 2012 about food additives, borax is a hazardous and toxic material banned as a food aditive. If borax used in a long time can caused many disease, especially cancer and dead. Lack of public knowledge about borax make they dont have preventif action to choose foods. Therefore, we interested to provide counseling with lecture and discussion method and then workshop which is participant come forward doing identification borax looking for shape, color, and smell and identification directly on food containing borax. The result of this service activity is understanding the society of Tebing Tinggi Okura about dangerous of borax in health increase and they know the characteristic of food containing borax. So, public more carefuly choosing the healthy food